Plasma hepcidin is associated with future risk of venous thromboembolism - Ellingsen, Trygve; Lappegård, Jostein; Ueland, Thor; Aukrust, Pål; Brækkan, Sigrid Kufaas; Hansen, John-Bjarne (Blood Advances, 2018)
Source at https://doi.org/10.1182/bloodadvances.2018018465 . Red cell distribution width (RDW) is associated with venous thromboembolism (VTE), but the underlying mechanism(s) is unclear. Iron deficiency is associated with high RDW, and studies suggest an association between iron deficiency and VTE. To assess whether iron deficiency is a risk factor for VTE that explains the association between RDW and VTE, we conducted a nested case-control study of 390 patients with VTE and 802 age- and sex-matched controls selected from the population-based cohort of the Tromsø Study. Physical measurements and blood samples were collected from 1994 to 1995. Logistic regression models were used to calculate odds ratios (ORs) with 95% confidence intervals (CIs) for VTE by RDW, hepcidin, and ferritin light chain (FtL). RDW was inversely associated with hepcidin, FtL, and hemoglobin. The risk of VTE increased linearly across categories of higher plasma hepcidin levels. Participants with hepcidin in the highest quartile had an OR for VTE of 1.32 (95% CI, 1.00-2.42), and those in the >90% percentile had an OR for VTE of 1.66 (95% CI, 1.14-2.42) compared with the reference group (quartiles 2 and 3). The risk estimates remained similar after adjustment for C-reactive protein. The risk of VTE increased by categories of higher RDW and was strengthened after inclusion of hepcidin and FtL in the multivariable model. Our findings reject the hypothesis that iron deficiency explains the association between RDW and VTE and suggest, in contrast, that high body iron levels might increase the risk of VTE.